Anterolateral Complex Reconstruction: Another Fad or Method to Improve ACL Outcomes?. Issue 4 (December 2018) - Wood, Ryan; Marsh, Jacquelyn; Getgood, Alan
Abstract : Anterolateral rotational laxity of the knee is a persistent problem following anterior cruciate ligament reconstruction (ACLR) that can lead to increased rates of graft failure. Renewed interest in the anterolateral complex of the knee has led to a resurgence in the use of adjunctive techniques such as lateral extra-articular tenodesis and anterolateral ligament reconstruction. Use of these techniques can restore normal knee kinematics and potentially thereby reduce the rate of graft failure. Historically, experience with modified ACLR techniques such as the double-bundle ACLR have shown that improved biomechanics is not always reflected in clinical outcome trials. Additional procedures also come with additional costs and further economic analysis needs to be performed to clarify whether these additional costs are offset by improved clinical and societal outcomes in the longer-term.